Misallocation and TFP loss - A Study of Public Bank Loans in Brazil - Silva, Natalia (Université d'Ottawa | University of Ottawa, 2017)
Misallocation is a well-studied topic among economists due to its potential effect on total factor (TFP). In this paper I use a direct approach to study the contribution of public bank loans distortions to TFP loss in Brazil in 2014 through an adaptation of a monopolistic competition model. My results suggest that removing these distortions would represent around 23% of TFP gain in Brazil; moreover diminishing the gap between public bank rates and private market rates would represent a reduction of about 52% in this measure in the same year.